Neuro-Endocrine Networks Controlling Immune System in Health and Disease - Procaccini, Claudio; Pucino, Valentina; De Rosa, Veronica; Marone, Gianni; Matarese, Giuseppe (Frontiers in Immunology, 2014)
The peripheral nervous and immune systems are traditionally thought of as serving separate functions. However, recent clinical and experimental data, together with epidemiological studies, have suggested that the pathogenesis of several immune-mediated disorders such as multiple sclerosis (MS) might involve factors, hormones, and neural mediators, that link the immune and nervous system. These molecules or their receptors are member of the same superfamily which enable the mutual and bi-directional neural-immune interaction. More recently, the discovery of leptin, one of the most abundant adipocyte-derived hormones that controls food intake and metabolism, has suggested that nutritional/metabolic status, acting at central level, can control immune self-tolerance, since it promotes experimental autoimmune encephalomyelitis, an animal model of MS. Here, we summarize the most recent advances and the key players linking the central nervous system, immune tolerance, and the metabolic status. Understanding this coordinated interaction may advance therapeutic approaches to increase host defense and suppress immunopathology.